1989
DOI: 10.1111/j.1432-1033.1989.tb15165.x
|View full text |Cite
|
Sign up to set email alerts
|

Neomycin induces high‐affinity agonist binding of G‐protein‐coupled receptors

Abstract: Neomycin, an inositol-phospholipid-binding aminoglycoside antibiotic, is known to interfere with signal transduction mechanisms involving phospholipase C as cffcctor enzyme. In this study, we report that neomycin can also markedly influence agonist binding of G-protein-coupled receptors. In membranes of differentiated human leukemia cells (HL 60 cells), neomycin (0.1 -10 mM) was found to induce high-affinity binding of the chcinotactic tripeptidc, N-formyl-methionylleucylphenylalanine (met-Leu-Phe), to its rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We have recently reported that Mg2 + markedly enhanced the number of high-affinity Met-Leu-Phe-binding sites in HL-60 membranes [27]. This effect was also elicited with other divalent cations such as Ca2+, Ba2' or Sr2+, and was even seen in response to polycations like the aminoglycoside antibiotic neomycin [41]. We now demonstrate that Mg2+ is both absolutely and specifically required to observe chemotactic agonist-stimulated, high-affinity [35S]GTP[S] binding to HL-60 membranes.…”
Section: Discussionmentioning
confidence: 87%
“…We have recently reported that Mg2 + markedly enhanced the number of high-affinity Met-Leu-Phe-binding sites in HL-60 membranes [27]. This effect was also elicited with other divalent cations such as Ca2+, Ba2' or Sr2+, and was even seen in response to polycations like the aminoglycoside antibiotic neomycin [41]. We now demonstrate that Mg2+ is both absolutely and specifically required to observe chemotactic agonist-stimulated, high-affinity [35S]GTP[S] binding to HL-60 membranes.…”
Section: Discussionmentioning
confidence: 87%
“…Our results further demonstrate that caution should be taken when using neomycin as a selective inhibitor of phosphoinositide hydrolysis (Siess and Lapetina, 1986;Nakashima et al, 1987;Polascik et al, 1987;Hermann et al, 1989). When added to intact cells, neomycin earl clearly interact with a membrane component that eventually activates phosphoinositide breakdown and histamine secretion.…”
Section: Discussionmentioning
confidence: 56%
“…For example, depending on its concentration neomycin wasshown to stimulate secretion, aggregation responses, and arachidonic acid release from semi-permeabilized platelets (Nakashima et al, 1987;Polascik et al, 1987). Neomycin was also shown to modify the activity of human platelet membrane GTPase (Hermann and Jakobs, 1988) and to induce high-affinity agonist binding of G protein-coupled receptors (Hermann et al, 1989). Therefore, to further investigate our hypothesis, in this study we have examined whether neomycin may activate secretion from mast cells in a mechanism that is independent of phosphoinositide breakdown.…”
mentioning
confidence: 99%
“…Under such a condition, neomycin, a PI-PLC inhibitor, significantly inhibited PC-PLD activity. Although neomy cin, an aminoglycoside antibiotic, is generally known for inhibiting PI-PLC by binding to inositol phospholipids [22,23], neomycin modifies the activity of platelet membrane GTPase [24] and induces high-affinity agonist binding of G protein-coupled receptors [25]. It also has been reported that neomycin inhib its GTPyS-induced histamine secretion and phosphatidic acid formation in permeabilized mast cells [26].…”
Section: Discussionmentioning
confidence: 99%